Transcatheter Left Atrial Appendage Occlusion: First Case of Nepal - Adhikari, Chandra Mani; Bogati, Amrit; Timalsena, Birat Krishna; Shahi, Ravi; Safi, Sajjad; Shrestha, Ram Kumar; Prajapati, Dipanker (Nepalese Heart Journal, 2025)
Transcatheter left atrial appendage occlusion (LAAO) is a valuable therapeutic option for stroke prevention in patients with non-valvular atrial fibrillation at high bleeding risk. Worldwide acceptance of LAAO therapy as an alternative to oral anticoagulation is growing. The most recent 2025 SCAI/HRS Clinical Practice Guidelines on Transcatheter Left Atrial Appendage Occlusion suggests Oral anticoagulation (OAC) or LAAO as treatment options for stroke prevention. While most patients are offered stroke prevention with OAC, those with elevated bleeding risk, prior bleeding complications, or strong preferences to avoid long-term anticoagulation would reasonably choose LAAO over OAC. In this case report we describe the first successful transcatheter LAAO in Nepal in a 75 years old male with CHA2DS2-VASc of 3 and HAS-BLED score of 3. Though he was treated with oral anticoagulation to prevent stroke but due to hemoptysis he could not continue it.TO prevent stroke patient party opted for the LAAO procedure. Under general anesthesia with Transesophageal echocardiogram guidance, patient underwent successful transcatheter LAAO with 31 mm Amulet device. He was discharged the next day of the procedure in stable condition without any complication.